1997
DOI: 10.1039/a704190j
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Ion-selective Electrodes Employing Tetrahydrofuran-based 16-Crown-4 Derivatives as Neutral Carriers

Abstract: The potentiometric response characteristics of lithium ion-selective membrane electrodes employing three different THF-type 16-crown-4 derivatives as ionophores were investigated. Of the THF-based crown compounds tested, a cis-type isomer of the derivative with only methyl groups (H/CH 3 ) at four bridged positions (cis-THF-I) was found to exhibit the best selectivity for Li + over other cations. The composition of the cis-THF-I-based PVC-matrix membrane was optimized and its performance was compared with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…29 The most interference of Li + ion for the THF-containing-16-crown-4-based NH 4 + -ISEs is due to the suitable ion size of lithium ion and geometric structure of the lithium-ionophore complex as previously reported. 20,21,29 The pH-dependence of the electrode was studied for the pH range 2.5-10.0, adjusted by addition of hydrochloric acid and potassium hydroxide solutions having the same NH 4 + concentration as the test solution. The potentiometric responses of E1 to different concentrations of NH 4 + at above pH range are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The most interference of Li + ion for the THF-containing-16-crown-4-based NH 4 + -ISEs is due to the suitable ion size of lithium ion and geometric structure of the lithium-ionophore complex as previously reported. 20,21,29 The pH-dependence of the electrode was studied for the pH range 2.5-10.0, adjusted by addition of hydrochloric acid and potassium hydroxide solutions having the same NH 4 + concentration as the test solution. The potentiometric responses of E1 to different concentrations of NH 4 + at above pH range are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we have reported that THF-containing crown ethers with small substituents (R=CH 3 , R'=H) at four bridged meso-carbon position show excellent sensitivity and selectivity for Li + ion. [19][20][21] In the course of our consecutive works for the Li + ionophores, we realized that the analogue with methyl groups (R=R'=CH 3 ) exhibited very high interference by NH 4 + ion. 19 This result motivated us to require further examination and then we became interested in the THF-containing crown ethers in the view of the development of new candidates for NH 4 + ionophores.…”
Section: Introductionmentioning
confidence: 99%
“…), and 27 (1.2% wt.) gave a Li + :Na + selectivity of 630:1 coupled to much improved selectivities for Li + over all other cations tested [ 41 ].…”
Section: Sensorsmentioning
confidence: 99%
“…Although ionophores have been considered early on, the synthetic ionophores with high affinity and selectivity for lithium ion is a challenging task. In this regard, considerable efforts have been given on crown ether derivatives, spherands, hemispherands, , metallamacrocycles, and various lithium ionophores/​receptors which often require substantial synthetic efforts.…”
Section: Introductionmentioning
confidence: 97%